Synthesis of Conformationally Locked and C-Linked Analogues of Imidazole-Based Ketene Dithioacetal Fungicides - Gagnepain, Julien; Jeanmart, Stephane; Bonvalot, Damien; Jacob, Olivier; Lamberth, Clemens (Synlett, 2019)
First examples with the unknown tricyclic 4,8b-dihydro-3aH-indeno[1,2-d][1,3]dithiole ring system have been prepared. Also, imidazoles linked in ring position 5 to a ketene dithioacetal and 1,3-dithiane derivatives with an exocyclic cyano- and imidazole-substituted C–C double bond are completely new. All these compounds are either conformationally locked, C-linked or six-ring analogues of the antifungal agent luliconazole. Synthesis and fungicidal activity of these sterol biosynthesis inhibitors are reported.
Keywords: dithiolane; imidazole; C14-demethylase inhibitor; fungicide